Identifikasi Jenis Burung di Hutan Adat Guguk Kecamatan Renah Pembarap Kabupaten Merangin Provinsi Jambi : Identification of Bird Species in Guguk Customary Forest, Renah Pembarap District, Merangin Regency, Jambi Province - Wulan, Cory; Pranesti, Ageng; Khabibi, Jauhar (Jurnal Silva Tropika, 2025)
ABSTRACT Guguk Customary Forest is one of the customary forests in Jambi Province with an area of 690 ha. It was designated as a customary forest starting 2003, through the Decree of the Regent of Merangin Number: 287 of 2003, on November 23, 2003 this customary forest located in Renah Pembarap District, Merangin Regency. This study was aim to identify various types of birds and analyze the diversity, evenness, richness and community similarities of bird species that have been carried out in 4 types of habitats (riparian river, mixed gardens, shrubs, and secondary forests) using point count and purposive sampling method. The total number of bird species in Guguk Customary Forest is 31 species of birds from 20 families. The results showed that the bird species diversity index (H ') is 3,14 (high diversity), the Richness index () is 5,13 (high), the Evenness Index (E) is 0,93 (even) and the results of calculations on the community similarity index show that the bird communities in the 4 habitat types are different.   Keywords: birds, diversity, Guguk customary forest   ABSTRAK Hutan Adat Guguk merupakan salah satu hutan adat di Provinsi Jambi dengan luas 690 ha. Hutan ini ditetapkan sebagai hutan adat mulai tahun 2003, melalui Keputusan Bupati Merangin Nomor: 287 Tahun 2003, tanggal 23 November 2003 hutan adat ini terletak di Kecamatan Renah Pembarap, Kabupaten Merangin. Penelitian ini bertujuan untuk mengidentifikasi berbagai jenis burung dan menganalisis keanekaragaman, kemerataan, kekayaan dan kesamaan komunitas jenis burung yang telah dilakukan pada 4 tipe habitat (sungai riparian, kebun campuran, semak belukar, dan hutan sekunder) dengan menggunakan metode point count dan purposive sampling. Jumlah jenis burung di Hutan Adat Guguk sebanyak 31 jenis burung dari 20 famili. Hasil penelitian menunjukkan bahwa indeks keanekaragaman jenis burung (H') sebesar 3,14 (keanekaragaman tinggi), indeks kekayaan () sebesar 5,13 (tinggi), indeks kemerataan (E) sebesar 0,93 (merata) dan hasil perhitungan pada indeks kesamaan komunitas menunjukkan bahwa komunitas burung pada 4 tipe habitat tersebut berbeda-beda.   Kata kunci: burung, Hutan Adat Guguk, keanekaragaman jenis